Phase space methods in open quantum systems - Kansanen, Kalle (2018)
In this work we extend the phase space approach of quantum mechanics to open quantum systems. Using the formalism of generalized coherent states and the time-dependent variational principle, phase space Langevin equations are derived for harmonic oscillator and spin systems. It is proved that the former is fully consistent with the quantum master equation. The latter, however, is an approximation that is accurate for large spin numbers or low temperatures.